LEFT VENTRICULAR LONGITUDINAL STRAIN INDICES ON 2D SPECKLE-TRACKING ECHOCARDIOGRAPHY IN PATIENTS WITH MITRAL STENOSIS (Vietnam Journal of Community Medicine, 2026)
Mitral stenosis is a common heart valve disease in Vietnam, characterized by the narrowing of the mitral valve orifice as a result of rheumatic valve damage. Early detection of left ventricular dysfunction in asymptomatic mitral stenosis patients is crucial. Myocardial speckle tracking echocardiography (STE) is a novel technique that can provide additional information beyond conventional ultrasound parameters and may assist physicians in assessing, risk-stratifying, and optimizing the timing of intervention or surgery for asymptomatic patients with severe mitral stenosis. The objective of the study: "To investigate the left ventricular longitudinal strain index (GLS) using 2D speckle tracking echocardiography in patients with mitral stenosis." The study revealed that the average left ventricular longitudinal strain value in the mitral stenosis patient group was significantly lower than the normal threshold (–21%), even though the left ventricular ejection fraction (EF) remained preserved. This impairment was unevenly distributed across regions, with a notable reduction observed in the basal and mid-left ventricular segments, while the apical region remained relatively preserved.
Keywords: mitral stenosis, speckle tracking echocardiography.